Nitrogen, Phosphorus, and Sulfur Tri-doped Carbon A Coated NiCo2Se4 Needle Arrays Grown on Carbon Cloth as Binder-free Anode for Potassium-Ion Batteries - Fan, Jinchen; Zheng, Yujun; Zhao, Zhongshu; Guo, Wenyao; Zhu, Sheng (Frontiers in Materials, 2022)
Bimetallic selenides are considered to be the promising high-capacity anode materials for potassium ion batteries (PIBs). However, the dramatic volume fluctuation of K+ ions and pulverization during cycling still limit their practical application in PIBs. Herein, the nitrogen, phosphorus, and sulfur tri-doped carbon (SPNC)-coated bimetallic NiCo2Se4 needle arrays grown on carbon cloth (NiCo2Se4⊂SPNC/CC) prepared as a binder-free anode for PIBs. The polyphosphazene (PSZ) was used as ingenious heteroatoms doping carbon source. The coated SPNC layer derived from the PSZ on the surfaces of NiCo2Se4 needle arrays not only effectively alleviate the volume expansion of NiCo2Se4 but also provide abundant active sites for the storage of K+ ions. As the PIB anode, the NiCo2Se4⊂SPNC/CC could deliver a high reversible capacity of 880.9 mAh·g-1 at a current density of 0.1 A·g-1. After 500 cycles, the NiCo2Se4⊂SPNC/CC anode still maintains a high reversible capacity of 268.1 mAh·g-1 at a current density of 0.5 A·g-1.